Cr K-edge X-ray absorption and FTIR spectroscopic study on the reaction mechanisms of Cr(III) and Cr(VI) with lignin. Issue 45 (25th September 2016) - Lin, Yu-Chi; Wang, Shan-Li
Abstract: The reaction mechanisms of lignin with Cr(III) and Cr(VI) were investigated using Cr K -edge X-ray spectroscopy (XAS) and FTIR spectroscopy. The spectroscopic results for lignin reacted with Cr(III) showed that the adsorbed Cr(III) has a coordination environment similar to that of ion, and the carbonyl groups of lignin are predominately responsible for adsorbing Cr(III). Accordingly, the reaction mechanism of Cr(III) with lignin was determined to be surface adsorption through the formation of an outer-sphere complex. In contrast, Cr(VI) reaction with lignin is not simply surface adsorption. Upon reaction with lignin, Cr(VI) was reduced to Cr(III), which was either bound to lignin or released back into solution. The corresponding FTIR spectra revealed that the carbonyl and phenolic groups are the primary sites for reducing Cr(VI) to Cr(III), leading to the formation of carboxyl groups. The carboxyl groups chelate Cr(III) to form a bidentate inner-sphere complex, deduced from the XAS and FTIR results. The formation of polynuclear Cr(III) species on the lignin surface after Cr(VI) reaction was also detected. The results of this study provide new insights into the reaction mechanisms of Cr(III) and Cr(VI) with lignin, and these new insights can be used to re-evaluate the results of macroscopic observations in the literature.